2021
DOI: 10.1007/s00248-021-01820-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Microbial Communities across the Life Stages of Nilaparvata lugens (Stål)

Abstract: Understanding the composition of microorganismal communities hosted by insect pests is an important prerequisite for revealing their functions and developing new pest control strategies. Although studies of the structure of the microbiome of Nilaparvata lugens have been published, little is known about the dynamic changes in this microbiome across different developmental stages, and an understanding of the core microbiota is still lacking. In this study, we investigated the dynamic changes in bacteria and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…39 YLSs, harbored in the abdomen fat-body cells of N. lugens, help the host survive on its nutrient-limited phloem diet by providing supplementary essential amino acids and sterols. [48][49][50][51] Therefore, fungicides may reduce the survival of BPHs by affecting some key symbionts. Our results found that tebuconazole significantly affected the structure of symbiotic fungi of N. lugens, including ⊍-diversity and ⊎-diversity, and dramatically changed the composition of symbiotic fungal communities of N. lugens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 YLSs, harbored in the abdomen fat-body cells of N. lugens, help the host survive on its nutrient-limited phloem diet by providing supplementary essential amino acids and sterols. [48][49][50][51] Therefore, fungicides may reduce the survival of BPHs by affecting some key symbionts. Our results found that tebuconazole significantly affected the structure of symbiotic fungi of N. lugens, including ⊍-diversity and ⊎-diversity, and dramatically changed the composition of symbiotic fungal communities of N. lugens.…”
Section: Discussionmentioning
confidence: 99%
“…YLSs, harbored in the abdomen fat‐body cells of N . lugens , help the host survive on its nutrient‐limited phloem diet by providing supplementary essential amino acids and sterols 48–51 . Therefore, fungicides may reduce the survival of BPHs by affecting some key symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple triatomines, microbial diversity gradually decreases with insect development [ 29 ]. In Nilaparvata lugens , microbial diversity remains stable throughout the life cycle [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 The major insect pest of rice crop, Nilaparvata lugens (Stål), has caused enormous losses to worldwide rice production. 4 Currently, chemical control remains the main approach to managing N. lugens in the field. 5 However, N. lugens has rapidly developed insecticide resistance due to the irresponsible application of insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, massive rice yield reductions due to rice insect pests and diseases have exacerbated the issue . The major insect pest of rice crop, Nilaparvata lugens (Stål), has caused enormous losses to worldwide rice production . Currently, chemical control remains the main approach to managing N.…”
Section: Introductionmentioning
confidence: 99%